A Study of Management Control Systems (MCS) and School Performance. Issue 2 (December 2017) - Baid, Devesh
The behaviour of students and teachers influences academic performance. Individual dimension of behaviour control, such as attendance of teachers and students in classrooms, students' indiscipline, remedial sessions by teachers to academically weak students, and teachers' education, have been found to influence academic performance. This study uses Merchant's (1998) objects of control framework to classify these individual behavioural controls into various control types, so as to identify the most prominent control types for students and teachers, and their influence on academic performance. It adopts alternative approaches of PLS-SEM using SMART PLS 3.2 to construct a "Management Control of Students' and Teachers' Scale". In all, 58 schools participated in this study. Based on school-level summated scores, it was found that action controls of students and personnel controls of teachers are the most prominent type of control applied in the schools. Also, teachers' control types relating to action controls—class conduct, results, and personnel controls of teachers—significantly influence academic performance at schools. In case of students' controls, their socio-economic status along with personnel controls is significant in explaining performance.